2018
DOI: 10.1038/s41396-018-0053-9
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma-related endobacteria within Mortierellomycotina fungi: diversity, distribution and functional insights into their lifestyle

Abstract: Bacterial interactions with animals and plants have been examined for over a century; by contrast, the study of bacterial-fungal interactions has received less attention. Bacteria interact with fungi in diverse ways, and endobacteria that reside inside fungal cells represent the most intimate interaction. The most significant bacterial endosymbionts that have been studied are associated with Mucoromycota and include two main groups: Burkholderia-related and Mycoplasma-related endobacteria (MRE). Examples of Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 78 publications
1
58
0
Order By: Relevance
“…This result suggests that the assembled De MREII and De MREI‐1 genomes are complete or nearly complete. The divergence of 16S rRNA sequences between De MREI‐1/ De MREI‐2 and De MREII is 15%, which exceeds the criterion proposed for species discrimination in Mollicutes (Desirò et al ., ). The divergence on a genomic scale is much higher: only 22% of De MREI‐1/ De MREI‐2 genomes show synteny with the De MREII genome (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This result suggests that the assembled De MREII and De MREI‐1 genomes are complete or nearly complete. The divergence of 16S rRNA sequences between De MREI‐1/ De MREI‐2 and De MREII is 15%, which exceeds the criterion proposed for species discrimination in Mollicutes (Desirò et al ., ). The divergence on a genomic scale is much higher: only 22% of De MREI‐1/ De MREI‐2 genomes show synteny with the De MREII genome (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The BRE are found only in the family Gigasporaceae (Bonfante & Desirò, ), and loss of BRE impairs fungal growth (Lumini et al ., ). By contrast, the MRE are distributed broadly among the AM fungi, but their functions are largely unknown, although a fitness cost has been demonstrated recently in Mortierella harboring MRE (Desirò et al ., ). The MRE population in AM fungi is diverse and, based on 16S rRNA phylogeny, there are two major phylotypes (Naumann et al ., ; Ghignone et al ., ; Bonfante & Desirò, ; Desirò et al ., ) that coexist in many AM fungal lineages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was largely unexpected, as molecular evolution patterns suggest that CaMg may be a parasite of AMF [13,14]. Moreover, there is experimental evidence indicating that endobacteria closely related to CaMg are conditional parasites of Mortierellomycotina, another group of Mucoromycota fungi [41]. Although the exact role of CaMg in the biology of AMF has not been established, two evolutionary scenarios could account for the persistence of a heritable parasite in AMF populations: (i) occasional horizontal transmission [42,43], and (ii) conditional mutualism [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the PLS-DA of the unidentified features ( (ESI) conditions bias the analysis towards polar and water-soluble metabolites. Whereas this paper is focused on the detection of polar metabolites, future profiling of the lipidome is also likely to yield valuable information, and previous reports have shown that lipids play a role in the endosymbiosis between the fungi and bacteria (Desirò et al 2018;Lastovetsky et al 2016;Pétriacq et al 2017).The detected features could be assigned to a number of compound classes: amino acids, nucleotides, organic acids, and sugars. Unidentified features that showed a high level of differentiation between groups could be further characterized to determine biological significance.…”
Section: Unidentified Components Of the Metabolomementioning
confidence: 99%